2016
DOI: 10.1200/jco.2016.34.4_suppl.672
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasma protein biomarkers from the phase 3 CONCUR study of regorafenib in Asian patients with metastatic colorectal cancer (mCRC).

Abstract: 672 Background: In the randomized phase 3 CONCUR trial (NCT01584830), regorafenib significantly improved overall survival (OS) and progression-free survival (PFS) vs placebo (PBO) in Asian patients (n = 136 regorafenib; n = 68 PBO) with treatment-refractory mCRC (HR [95% CI]: OS 0.55 [0.40‒0.77]; PFS 0.31 (0.22‒0.44]). Protein biomarker data from the phase 3 CORRECT trial of mostly Western patients with mCRC identified TIE-1 as a potential predictor of clinical response to regorafenib; however, this associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Multiple potential prognostic markers were identified in LCCC1029 trial and the Italian cohort with a high degree of consistency. Our finding that PlGF is a negative prognostic marker in LCCC1029 is consistent with the CORRECT report (15), while the finding that Ang-2 is a negative prognostic marker in the Italian cohort is consistent with the CONCUR report (16).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Multiple potential prognostic markers were identified in LCCC1029 trial and the Italian cohort with a high degree of consistency. Our finding that PlGF is a negative prognostic marker in LCCC1029 is consistent with the CORRECT report (15), while the finding that Ang-2 is a negative prognostic marker in the Italian cohort is consistent with the CONCUR report (16).…”
Section: Discussionsupporting
confidence: 91%
“…However, to the best of our knowledge, circulating protein biomarkers have not been well-studied in patients receiving regorafenib in later-line settings. While a few prognostic markers were suggested in CORRECT (15) and CONCUR trials (16), no predictive biomarkers have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Another subgroup analysis of the CORRECT study revealed that K-RAS and PIK3CA mutations were favorable prognostic factors for survival [ 20 ]. In addition, other subgroup analyses identified several prognostic biomarkers [ 21 ]. In real-world experiences, the potential prognostic factors were poor ECOG PS, a short time from the initial diagnosis of metastases to the start of regorafenib treatment (<160 mg), >3 metastatic sites, the presence of liver metastases, and the presence of K-RAS mutations [ 11 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…CEA has been routinely employed as a surrogate marker to detect early recurrence for patients with localized CRC who underwent surgical resection [22]. For advanced mCRC, the level of CEA has shown an inverse correlation with poor survival despite patients receiving therapy aggressively [23][24][25].…”
Section: Discussionmentioning
confidence: 99%